ASPEK MANAGERIAL KEBIJKAN DINAS PEKERJAAN UMUM DAN PENATAAN RUANG DALAM PENGENDALIAN BANJIR DI KOTA SAMARINDA - Effendy, Izrulsyah (Jurnal Administrative Reform, 2022)
This article will discuss managerial aspects in implementing flood control policies by the PUPR Office of Samarinda City as seen from four policy implementation variables, namely communication, resources, disposition, and communication. The research method used is qualitative. Data were collected through observation, interviews, and literature study—data analysis using interactive data analysis. The study results indicate that the managerial aspects of the four policy implementation variables in the implementation of flood control policies have been running quite well. In some cases, there are still obstacles.Keyword: managerial aspect, policy, flood control